2022
DOI: 10.1101/2022.02.25.481991
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Combined Human Gastruloid Model of Cardiogenesis and Neurogenesis

Abstract: Multi-lineage development from gastruloids is enabling unprecedented opportunities to model and study human embryonic processes and is expected to accelerate ex vivo strategies in organ development. Reproducing human cardiogenesis with neurogenesis in a multi-lineage context remains challenging, requiring spatiotemporal input of paracrine and mechanical cues. Here we extend elongating multi-lineage organized (EMLO) gastruloids to include cardiogenesis (EMLOC) and describe interconnected neuro-cardiac lineages … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
(70 reference statements)
0
2
0
Order By: Relevance
“…Many groups are recapitulating aspects of embryogenesis of organs ex vivo in hPSC organoid and gastruloid technologies ( Simunovic and Brivanlou, 2017 ). This includes early gastruloid models with regions expressing cardiogenic and heart field markers ( Rossi et al, 2020 ) as well as complex multi-chambered and innervated human hearts ( Olmsted and Paluh, 2022 ). Schultheiss et al (1997) revealed that bone morphogenic protein 4 (BMP4) was required for myocardial differentiation during early embryonic development in ESCs.…”
Section: Engineering 3d Hpsc-derived Heart Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many groups are recapitulating aspects of embryogenesis of organs ex vivo in hPSC organoid and gastruloid technologies ( Simunovic and Brivanlou, 2017 ). This includes early gastruloid models with regions expressing cardiogenic and heart field markers ( Rossi et al, 2020 ) as well as complex multi-chambered and innervated human hearts ( Olmsted and Paluh, 2022 ). Schultheiss et al (1997) revealed that bone morphogenic protein 4 (BMP4) was required for myocardial differentiation during early embryonic development in ESCs.…”
Section: Engineering 3d Hpsc-derived Heart Modelsmentioning
confidence: 99%
“…Wnt activation is also applied in the elongating multilineage organized cardiac (EMLOC) advanced heart gastruloid. All-in-all, the current novel state of cardiac organ gastruloids in mice ( Rossi et al, 2020 ) and humans ( Olmsted and Paluh, 2022 ) are largely focused on heart development and congenital heart defects and cardiotoxicity screening of drugs has not yet been explored.…”
Section: Engineering 3d Hpsc-derived Heart Modelsmentioning
confidence: 99%